2013
DOI: 10.1590/s0103-51502013000300009
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and learning curves of inexperienced observers for manual segmentation of electromyograms

Abstract: INTRODUCTION: The shape-varying format of surface electromyograms introduces errors in the detection of contraction events. OBJECTIVE: To investigate the accuracy and learning curves of inexperienced observers to detect the quantity of contraction events in surface electromyograms. MATERIALS AND METHODS: Six observers performed manual segmentation in 1200 shape-varying waveforms simulated using a phenomenological model with variable events, smooth changes in amplitude, marked on-off timing, and variable signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Thus, although there is no standard method to evaluate the quality of sEMG and based on our findings, we recommend the use of quantitative measures such as the SNR to evaluate the sEMG signal quality. Automated methods of onset and offset detection are fast and accurate, 18 but they require deeper knowledge of computational routine programming for more specific analysis. Differently, the visual inspection method of the onset and offset of contraction is subjective and dependent on the rater's experience, despite its convenience for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, although there is no standard method to evaluate the quality of sEMG and based on our findings, we recommend the use of quantitative measures such as the SNR to evaluate the sEMG signal quality. Automated methods of onset and offset detection are fast and accurate, 18 but they require deeper knowledge of computational routine programming for more specific analysis. Differently, the visual inspection method of the onset and offset of contraction is subjective and dependent on the rater's experience, despite its convenience for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, a relationship between qualitative and quantitative evaluation was found, i.e., the higher the SNR, the better the signal quality. According to Ferreira et al 18 accuracy for determining sEMG events by visual inspection is low when the SNR is low. Thus, although there is no standard method to evaluate the quality of sEMG and based on our findings, we recommend the use of quantitative measures such as the SNR to evaluate the sEMG signal quality.…”
Section: Discussionmentioning
confidence: 99%